Regulación del turismo espacial en el derecho del espacio ultraterrestre con relación al principio de cooperación (2017)
This research project was carried out taking into account its relevance for current outer space law. In recent years, there has been an increase in missions to outer space - by both astronauts and tourists - which is why all kinds of problems are likely to arise. These must be faced by States, which will not have clarity about their obligations in cases of emergency. Thus, the following research question was posed: What innovations are required in the international legal order of outer space law from 1957 to date to ensure the efficient operation of space tourism?